The Quintessence of Supply Chain Management What You Really Need to Know to Manage Your Processes in Procurement, Manufacturing, Warehousing and Logistics - Poluha, Rolf G. (Quintessence Series, 2016)
In the Future, Competition will be between Supply Chains. This book describes the fundamentals of Supply Chain Management in clear and concise terms. It explains why in the near future real competition is going to be between supply chains and what the consequences will be. Managers and decision-makers will be able to build on their business's competitive advantage with the essentials provided in this work. The focus here is upon what you really need to know in order to optimally manage your processes in procurement, manufacturing, warehousing and logistics. In addition to a wealth of illustrations and examples, valuable suggestions for further expansive reading are included. Essential insights are provided into how to analyse and evaluate the supply chain, based upon key aspects from research and practice, which helps readers to initiate their own optimisation processes.  »This book provides a compact review of Supply Chain Management and includes a clear overview of the most recent developments.« Dr. Paul Hofmann, Chief Technology Officer, Space-Time Insight, San Mateo.